Back Order dan Lost Sales sebagai Tantangan Ekonomi: Tinjauan Literatur terhadap Dampak dan Kebijakan Mitigasi - Pandega, Caesar Seta; Permana, Enda; Okitasari, Hanissa (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Supply Chain Management (SCM) is a critical element for industries operating in highly competitive environments. Among its most pressing challenges are inventory disruptions caused by back orders and lost sales, which not only raise operational costs but also undermine customer satisfaction and corporate reputation. This paper presents a systematic literature review (SLR) examining inventory policies and mitigation strategies related to back orders and lost sales. A total of 35 peer-reviewed articles published between 2010 and 2024 were selected from major databases such as SCOPUS, ScienceDirect, and IEEE. The review identifies four major mitigation strategies: maintaining adequate safety stock, implementing multi-echelon inventory systems, applying multi-sourcing approaches, and optimizing inventory rationing policies. Multi-echelon systems are shown to be effective in distributing inventory across different levels of the supply chain, reducing the frequency and cost of back orders. Multi-sourcing, meanwhile, enhances supply flexibility by relying on multiple vendors to prevent disruptions. Additionally, inventory rationing policies—such as continuous and periodic review systems—play a key role in determining replenishment strategies that balance service levels and cost. The findings suggest that combining these strategies significantly improves inventory resilience and performance. This review also highlights research gaps in lost sales modeling, especially in multi-echelon environments, and calls for more empirical studies to validate proposed frameworks.